The assessment of headache and sleep quality in patients with chronic obstructive pulmonary disease - Eren, Fettah; Özkan Bakdık, Bengü; Demir, Aysegul (Journal of Surgery and Medicine, 2022)
Background/Aim: It is known that sleep disorders and headaches are related. However, there are only very few studies examining this correlation in chronic obstructive pulmonary disease (COPD). The aim of this study was to evaluate the association between sleep disorders, headaches, and hypoxia in COPD patients. Methods: This study was designed as a prospective case-control study with 120 COPD and 83 controls patients of similar age/gender. International classification of headache disorders - version 3 (ICHD III) was used for the diagnosis of headache. Pain intensity was calculated using the visual analog scale (VAS). For the effect of headache, headache activities of daily living index (HADLI) questionnaire was applied. Pulmonary function tests were performed with a PC-based spirometry device. Blood pressure and blood oxygen saturation were measured by fingertip pulse oximetry. Sleep quality was assessed using the Pittsburgh sleep quality index (PSQI). Dyspnea severity was graded according to the modified medical research council (mMRC) scale. Results: Headache was detected in 54 patients (45%) with COPD. The most common type of headache was tension type (66.7%). Patients with headache had higher diastolic blood pressure, severity of dyspnea score, and lower forced expiratory volüme-1 (FEV1), forced vital capacity (FVC) (P = 0.037, P = 0.001, P = 0.001, P = 0.001 respectively). Sleep disturbance was quite common in COPD patients (79.2%). PSQI score was higher in patients with headache (P = 0.006). Patients with poor sleep quality had higher pain severity (P = 0.006). Female gender, high diastolic blood pressure and low forced expiratory volume-1 second (FEV1) increased the risk of headache (P = 0.004, P = 0.02, P = 0.032, respectively). Conclusion: Headache is a complex symptom in patients with COPD and associated with higher diastolic blood pressure and pulmonary dysfunction. These parameters should be evaluated in COPD patients with headache.